Two synchronous malignancies: nodular melanoma and renal cell carcinoma in a patient with an underlying germline BRCA2 mutation. Issue 6 (20th June 2019) - Snow, Anson; Ricker, Charite; In, Gino K
Abstract : Modernised genetic testing among patients with cancer has led to an increasing wealth of knowledge regarding cancer biology and aetiology. Furthermore, some germline mutations have the potential to direct therapeutic approaches as well. While BRCA1/2 mutations are well-established risk factors for breast and ovarian cancers, their impact on other cancers is less understood. We describe a patient with a germline BRCA2 mutation who developed synchronous melanoma and renal cell carcinoma, but responded well to treatment and is now cancer free.